Hitler : a study in tyranny - Bullock, Alan, 1914-2004. (New York : Harper & Row, 1962)
The sources for this exhaustive study included the massive German archives, evidence given at the Nuremberg trials, and countless documents, speeches, memoirs and diaries of men in close contact with the Fuhrer.
Party leader, 1889-1933. The formative years, 1889-1918 ; The years of struggle, 1919-24 ; The years of waiting, 1924-31 ; The months of opportunity, October 1931-30 January 1933 -- Chancellor, 1933-9. Revolution after power, 30 January 1933-August 1934 ; The counterfeit peace, 1933-7 ; The dictator ; From Vienna to Prague, 1938-9 ; Hitler's war, 1939 -- War-lord, 1939-45. The inconclusive victory, 1939-40 ; 'The world will hold its breath', 1940-41 ; The unachieved empire, 1941-3 ; Two Julys, 1943-4 ; The emperor without his clothes.
Includes bibliographical references (pages 809-815) and index.
Keywords: Hitler, Adolf, -- 1889-1945.; National socialism; Germany -- Politics and government -- 1933-1945.